Optical Absorption Enhancement in Polymer BHJ thin Film Using Ag Nanostructures: A Simulation Study - Khalil, Asma; Ahmad, Zubair; Touati, Farid; Masmoudi, Mohamed (Current Nanoscience, 2020)
Background: The photo-absorption and light trapping through the different layers of the organic solar cell structures are a growing concern now-a-days as it affects dramatically the overall efficiency of the cells. In fact, selecting the right material combination is a key factor in increasing the efficiency in the layers. In addition to good absorption properties, insertion of nanostructures has been proved in recent researches to affect significantly the light trapping inside the organic solar cell. All these factors are determined to expand the absorption spectrum and tailor it to a wider spectrum. Objective: The purpose of this investigation is to explore the consequence of the incorporation of the Ag nanostructures, with different sizes and structures, on the photo absorption of the organic BHJ thin films. Methods: Through a three-dimensional Maxwell solver software, Lumerical FDTD, a simulation and comparison of the optical absorption of the three famous organic materials blends poly(3- hexylthiophene): phenyl C71 butyric acid methyl ester (P3HT:PCBM), poly[N-9″-heptadecanyl-2,7- carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)]: phenyl C71 butyric acid methyl ester (PCDTBT:PCBM) and poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene)-alt- 4,7-(2,1,3-benzothiadiazole)]: phenyl C71 butyric acid methyl ester (PCDPDTBT:PCBM) has been conducted. Furthermore, FDTD simulation study of the incorporation of nanoparticles structures with different sizes, in different locations and concentrations through a bulk heterojunction organic solar cell structure has also been performed. Results: It has been demonstrated that embedding nanostructures in different locations of the cell, specifically in the active layer and the hole transporting layer had a considerable effect of widening the absorption spectrum and increasing the short circuit current. The effect of incorporation the nanostructures in the active layer has been proved to be greater than in the HTL. Furthermore, the comparison results showed that, PCDTBT:PCBM is no more advantageous over P3HT:PCBM and PCPDTBT:PCBM, and P3HT:PCBM took the lead and showed better performance in terms of absorption spectrum and short circuit current value. Conclusion: This work revealed the significant effect of size, location and concentration of the Ag nanostructures while incorporated in the organic solar cell. In fact, embedding nanostructures in the solar cell widen the absorption spectrum and increases the short circuit current, this result has been proven to be significant only when the nanostructures are inserted in the active layer following specific dimensions and structures.
Keywords: absorbance spectrum